PEMANFAATAN LIMBAH DAUN BAWANG DAYAK (Eleutherine palmifolia L. Merr) SEBAGAI KRIM ANTI AGING DENGAN EMULGATOR ANIONIK DAN NONIONIK - Eka Kumalasari; Erna Prihandiwati (Jurnal Insan Farmasi Indonesia, 2019)
Dayak onions (Eleutherine palmifolia L. Merr) are typical plants of Borneo. Pharmacologically the part tubers are proven to have a therapeutic effect. Dayak onions grow in the tropics, one of which is in the Petuk Katimpun area of ​​Palangkaraya, Central Borneo, where there land are vast Dayak onion large farms. After harvesting Dayak onions will produce agricultural waste in the form of leaves that are not utilized and left to rot. Dayak onions leek waste extract contains flavonoid compounds and has antioxidant potential. Dayak onions antioxidants can be used to inhibit the aging of the skin and as an alternative to synthetic antioxidants which are harmful to health. Waste extract has a very strong antioxidant activity with an IC50 value of 45.33 ppm. On this basis, was made four cream formulas are made with different bases. Based on the physical test results all over formulas meet the good cream requirements. Formula III is a the formula with the damping antioxidant reduction the very biggest that is 63.84% ± 0.0891.